G478(P) The uncertain and the incidental: off-target variants in neonatal array comparative genomic hybridisation. (24th May 2017) - Burke, K; Dalton, J; Jose, S; Morgan, S
Abstract : Aims: Genomic technologies, such as array comparative genomic hybridisation (aCGH) and whole genome/whole exome (WG/ WES) sequencing, have transformed our ability to provide a genetic diagnosis for a range of common presentations of childhood, including congenital anomalies, developmental delay and autistic spectrum disorders. Associated with the use of genomewide technologies are the management of 'off-target' information – incidental genetic findings with known clinical sequela, and uncertain information – variants where the clinical implications are currently unknown (variants of uncertain significance). Decisions around how and when to share this information with families has significant ethical, legal, social and practical implications. For paediatric and neonatal patients, these issues are especially complex when considering the potential future implications of these results and the consequences for (future) autonomy. How frequently are these type of genetic variants identified in the neonatal population? Method: Retrospective audit of all aCGH requests received by the regional cytogenetic laboratory for neonatal patients in a 12 month period. Results: 339 requests for aCGH in neonatal patients were received. 16 requests were rejected as 'inappropriate requests'. 323 samples were processed. 23 samples failed to reach quality control standards and were not reported. 300 clinical reports were issued. 255 (85%) patients had no clinically significant variants identified. In 45 patients (15%), a clinically significant variant was identified: 22 (7.3%) of which had a clear association with the phenotype described (pathogenic), 19 (6.3%) of which were classified as variants of uncertain significance, and 4 (1.3%) of which were not associated with the presenting phenotype (incidental findings). Conclusion: Variants of uncertain significance and incidental findings are frequently identified when array CGH is undertaken for neonatal patients. Variants of uncertain significance account for 42% of reported variants in this patient group. The consequences for pre-test counselling are important: parents and families should be prepared that genetic technologies can contribute to, as well as resolve, uncertainty. More work is needed to ascertain the consequences of uncertain and incidental information, both for the clinical management and lived experience of patients and families, particularly as the frequency with which incidental and uncertain genetic information are encountered will increase as sequencing technologies transition from bench-to-bedside.